Effective scale-up: avoiding the same old traps - Nelson David; Gaye Pape A (BMC, 2009)
Abstract Despite progress in developing more effective training methodologies, training initiatives for health workers continue to experience common pitfalls that have beset the overall success and cost-effectiveness of these programs for decades. These include lack of country-level coordination of health training, inequitable access to training, interrupted services, and failure to reinforce skills and knowledge training by addressing other performance factors. These pitfalls are now seen as aggravating the current crisis in human resources for health and impeding the effective scale-up of training and the potential impact of promising strategies such as task shifting to address health worker shortages. Drawing on IntraHealth International's lessons learned in designing reproductive health and HIV/AIDS training and performance improvement programmes, this commentary discusses promising practices for strengthening human resources for health through more efficient and effective training and learning programmes that avoid the same old traps. These promising practices include the following: Assessing performance gaps and opportunities before designing a training initiative; addressing performance factors other than skills and knowledge that health workers need to perform well; applying a "learning for performance" approach; standardizing curricula throughout a country; linking pre-service education, in-service training and professional associations; enhancing traditional education; strengthening human resources information systems to improve workforce planning, policies and management; applying technology to meet training needs.